Kualitas Minyak Kayu Putih Hasil Penyulingan Daun Asteromyrtus symphiocarpa pada Musim Hujan dan Kering (The Quality of Cajuput Oil Distilled from the Leaves of Asteromyrtus symphiocarpa on Rainy and Dry Season) - Ary Widiyanto; Aji Winara; Edy Junaidi; Mohamad Siarudin; Yonky Indrajaya (Masyarakat Peneliti Kayu Indonesia, 2017)
Wasur National Park, located in Merauke Regency, Papua, has various vegetation that could potentially yield cajuput oil, particularly those originated from Myrtaceae family. Among those are Asteromyrtus symphiocarpa. This research aimed to analysis the quality of cajuput oil distilled from the leaves of A. symphiocarpa. Initially, some amounts of leaves sample were plucked, either in the rainy and dry season. The distillation took place in the batch kettle, and each batch was charged of 12 kg of each fresh leaves. The distillation lasted for 4-5 hours, and every 30 minutes, the distilled oil was collected cumulatively. The cajuput oil from the leaves plucked on rainy season afforded the yield of 0.16%, specific gravity of 0.943, refractive index of 1.462, solubility in alcohol 1:1, optical rotations -5.2, and cineole content of 68%. Meanwhile, the corresponding value from those plucked in dry season were 0.33%, 0.912, 1.459, 1:1, -2.1, and 80%, respectively. The qualities of the overall cajuput oil from A. symphiocarpa leaves could satisfy the SNI 06-3954-2006 and belonged the main (U) class. With higher yield and greater cineole content, the cajuput oil obtained from the dry season’s leaves exhibited better qualities; hence it is more potential to be developed commercially.Keywords: Asteromyrtus symphiocarpa leaf, cajuput oil, dry season, rainy seasons.